Editorial - Martha Cleveland-Innes; Sawsen Lakhal (The Canadian Network for Innovation in Education (CNIE), 2021)
As the COVID-19 pandemic slowly subsides, this journal, which focuses on learning and technology, is overwhelmed with article submissions. The education response to the health and safety requirements of the pandemic included the use of new technologies for learning in many education spaces and geographic places. Suffice to say that the interest in the topic of technology-enabled learning has increased exponentially. Over the last year we have received more than double our usual number of submissions. While an exciting transformation in the field of education, we were unprepared for the influx. Many of our authors and reviewers work in some sector of education, as does the editorial team of the journal. Currently caught up with our response to submissions, there continues to be some delay in securing agreement and support from reviewers, many of whom are still dealing with the demand on education to continue near-normal delivery. As interest and expertise in the field develops, and with hope that the pandemic continues to subside, we expect to see these recent time delays diminish over the next year.